Comparative Study of Leadership Styles in Public and Private Elementary Schools - Parlin Djumiastin; Hitta Alfi Muhimmah; Heru Subrata (Sekolah Tinggi Ilmu Al-Qur'an (STIQ) Amuntai Kalimantan Selatan, 2025)
Effective leadership has emerged as a crucial focus within the framework of Merdeka Belajar, a policy that enhances the capacity of educational institutions to innovate and respond to the specific needs of their local communities. The influence of leadership on educational outcomes is profound, affecting both educator performance and the institution's overall effectiveness. A principal who exemplifies strong leadership can significantly enhance teacher effectiveness and improve student achievement. This research seeks to analyze the differing leadership styles of principals in public versus private elementary schools during the Merdeka Belajar initiative. Employing a comparative methodology, the study gathers data through interviews, questionnaires, and observations involving principals, teachers, and staff from both sectors. Findings indicate that public schools generally adopt a transactional leadership approach, whereas private schools are more inclined towards transformational leadership. The study aims to offer valuable insights, suggesting that both public and private institutions should embrace a more adaptable leadership style. In public schools, it is recommended that principals foster a culture of innovation and actively seek input from diverse stakeholders, thereby creating a more collaborative environment for teachers and students alike.